Challenges to Effective Public Affairs Communication - Pokhrel, Prabal Raj (Socio-Economic Development Panorama, 2008)
The article deals with the historical aspects of the advent of public affairs system in the Western and the Eastern worlds and portrays its successes and weaknesses in Nepal. It then amplifies the functions of the organizations blending it with information and communication science as its tools. It underlies that information is a multiplier of power where control and equal access to communication is much more important than the physical forces. It advocates that only an effective communicative behaviour can democratically channel human actions and capacity building in organizations. The challenges to creation of a New Nepal is that the people centered information policy needs to oversee national welfare promotion, sovereignty, security, utility emancipation and development values reflected in a democratic communication in the organizations. Effective communication is reflected in fostering understanding, encourage ideas, improve and manage communicative relations through various systems in cluster. The query is how can media associate itself effectively as the mediator, arbitrator, conciliator and consultant for realization of a democratic, equitable public affairs system? The article attempts to analyze how communication is a tool of supervision as a nerve center for human discourse which helps in planning supervision and establishing linkages for creation of a democratic people centered work culture system to enhance effective public affairs system. Socio-Economic Development Panorama, Vol. 1, No. 2(2007) pp. 93-99